Pengaruh Total Hutang dan Besarnya Modal Sendiri Terhadap PerolehanEarning per sharePada PT. BFI Finance yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2007-2016 - Susi Artati (Universitas Batanghari, 2018)
This research aims to find out how the influence of total debt and own capital against the Earning per share simultaneously and partial PT. BFI Finance Tbk 2007-2016 period. This research uses descriptive quantitative methods with multiple linear regression analysis technique. The result of the research shows Fhitung of 8,878 > Ftabel of 4.74 to suggest that the presence of the influence of total debt and own capital against the Earning per share simultaneously, while partially no influence of independent variable i.e. the total debt (X 1) and private equity (X 2) against the Earning per share (Y). Keyword: debt, finance